2011
DOI: 10.1002/ar.21428
|View full text |Cite
|
Sign up to set email alerts
|

High‐Intensity Resistance Training with Insufficient Recovery Time Between Bouts Induce Atrophy and Alterations in Myosin Heavy Chain Content in Rat Skeletal Muscle

Abstract: The aim of this study was to test whether high-intensity resistance training with insufficient recovery time between bouts, could result in a decrease of muscle fiber cross-sectional area (CSA), alter fiber-type frequencies and myosin heavy chain (MHC) isoform content in rat skeletal muscle. Wistar rats were divided into two groups: trained (Tr) and control (Co). Tr group were subjected to a high-intensity resistance training program (5 days/week) for 12 weeks, involving jump bouts into water, carrying progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
0
16
0
2
Order By: Relevance
“…In most existing models of resistance exercise, dynamic movements of the hindlimbs are motivated by electric shock, such that the subject must repeatedly jump to escape or avoid the shock (Fluckey et al, 1995; Hernandez et al, 2000; Nilsson et al, 2010; Tamaki et al, 1992). In other models, subjects are placed in a weighted vest and submerged in water, requiring the animal to jump repeatedly to the surface in order to breathe (Cunha et al, 2005; De Souza et al, 2011; Haraguchi et al, 2011). The use of these methods limits the appeal of these models because repeated exposure to pain (e.g., electric shock) and stress (e.g., water submersion) can confound behavioral and neurobiological measures relevant to substance use.…”
Section: Introductionmentioning
confidence: 99%
“…In most existing models of resistance exercise, dynamic movements of the hindlimbs are motivated by electric shock, such that the subject must repeatedly jump to escape or avoid the shock (Fluckey et al, 1995; Hernandez et al, 2000; Nilsson et al, 2010; Tamaki et al, 1992). In other models, subjects are placed in a weighted vest and submerged in water, requiring the animal to jump repeatedly to the surface in order to breathe (Cunha et al, 2005; De Souza et al, 2011; Haraguchi et al, 2011). The use of these methods limits the appeal of these models because repeated exposure to pain (e.g., electric shock) and stress (e.g., water submersion) can confound behavioral and neurobiological measures relevant to substance use.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a submersion procedure in which the subject is placed at the bottom of a shallow pool with a weighted harness is a common water-based resistance model (e.g., Cunha et al, 2005; de Souza et al, 2011; Haraguchi et al, 2011). In this model, the subject is submerged in water with progressively increasing loads attached to a weighted vest and must jump in order to escape the water.…”
Section: Animal Models Of Resistance Exercisementioning
confidence: 99%
“…For this purpose, we used a 12-week resistance training program ( Figure 1), according to a protocol previously used in our laboratory, to induce muscle overwork and consequent atrophy in plantaris muscle fast-twitch fibers (e.g., type IIA and IID fibers) (9). The intensity and volume of training were progressive throughout the experiment (Table 1), achieving an overload 15% greater than what is recommended to promote beneficial adaptations in rat skeletal muscle (e.g., muscle fiber hypertrophy) (2).…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…Our laboratory recently reported that a resistance training program with insufficient recovery time between bouts can induce atrophy and phenotypic alterations in rat skeletal muscle fibers (9), which indicates an increase in the protein catabolism/anabolism ratio. In this regard, Petibois et al (31) observed that overtrained individuals presented higher amino acid levels and lower blood protein accumulation in response to exercise compared with appropriately trained individuals, which suggested that proteins were catabolized for amino acid supply during exercise.…”
Section: Introductionmentioning
confidence: 99%